The Utilization of Liquid Organic Fertilizer JAKABA (Eternal Lucky Mushroom) and Refugia Plants in Pest Control and Rice Productivity Improvement on Saline Land in Percut Village - Nur Ulina Warnisyah Sebayang; Julieta Christy; Rouzatul Nafisah; Reisy Tane; Ahmad Rusdi Tarihoran (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The main problem faced by the Sumber Rejeki Farmers Group in Percut Village, Percut Sei Tuan District, is the low productivity of rice due to saline land and pest infestations. The high soil acidity and low fertility are the main factors hindering rice growth. To address this issue, the community service team from Universitas Sumatera Utara (USU), in collaboration with student activity units, Himadita Nursery, implemented a program utilizing Liquid Organic Fertilizer (LOF) Jakaba (Eternal Lucky Mushroom) and planting refugia plants. LOF Jakaba, derived from mushroom cultivation, helps reduce soil acidity and increases essential nutrients, thereby improving soil structure. Meanwhile, refugia plants serve as habitats for natural pest predators, enabling ecological pest control and reducing reliance on chemical pesticides. The methods used in this program included socialization, training, and assistance for farmers in producing and applying LOF Jakaba, as well as planting refugia plants. The results of this initiative showed improved soil fertility, reduced pest infestations, and increased rice productivity. The conclusion of this activity is that this sustainable agricultural approach has the potential to serve as a model for other areas facing similar challenges and can enhance the well-being of farmers in Percut Village.